WAYANG WALI SEBAGAI BENTUK AKULTURASI BUDAYA ISLAM JAWA DI KABUPATEN BLITAR - Wijayanti, M.Pd, Jamila; Budiana, Nia; Dewi, Putri Kumala (University of Brawijaya, 2022)
Wayang is a type of theatrical performance that is typical in Indonesia. Wayang Wali is one of the new puppet creations developed by Ki Sudrun from Blitar. This puppet is unique because it has several characteristics that are different from the wayang in general. These characteristics include: First, Wayang Wali has the names of characters that are different from other types of puppets. Second, raw materials from leather and wood. Third, the story play is not standard. Fourth, the songs sung in wayang wali are not limited to Javanese songs. Fifth, the musical instruments used to accompany the wayang wali consist of Javanese gamelan, modern musical instruments (guitar, keyboard, drums), and flying.This research is a type of qualitative research with a descriptive approach. Data collection techniques were obtained by recording stories, observations, in-depth interviews, transcription (transfer from oral to written), and translation. The data analysis technique in this study was carried out by looking at the wayang wali performance, studying, understanding the characteristics of the form and content of the performance, as well as the form of acculturation of Javanese Islam in the wayang wali.Based on the results of the research, the Wayang Wali in terms of its shape has the characteristics of its material using leather and wood. Judging from the characteristics of its contents, the wayang wali with the story